Nudging' health behavioural change: behavioral economics, Tobacco control and innovative finance for Cancer control - Chilwesa, Mambwe (Graduate School of Business (GSB), 2025)
Tobacco smoking is the leading cause of preventable death globally. Despite the existing traditional economic approaches like taxation, recent progress in tobacco control has plateaued compared to control efforts in nutrition, sexual reproductive health and alcohol. This discrepancy can be attributed to better nudging efforts in these areas compared to tobacco control. This study aimed to determine the knowledge of tobacco-related health and social problems, applications of behavioural economics in tobacco control amongst tobacco-control stakeholders, and to identify innovative ways of funding for treatment of tobacco-related cancers. This exploratory, cross-sectional, qualitative study was conducted between January 2020 and December 2022. The data collection involved semi-structured interviews and a focus group meeting. Data analysis was done using the thematic semantic analysis approach, with the initial step including verbatim transcription of the interviews followed by the listing of emerging ideas, code generation and sorting of themes. The results demonstrated participants' extensive knowledge of tobacco-related health and social problems and their minimal understanding of behavioural economics including nudging in this space. A few behavioural economics principles were identified which included incentives, bounded rationality, goal gradient theory, gamification, hyperbolic discounting, and herd mentality. Findings also revealed innovative ways to fund the control of tobacco-related cancer, which included public-private partnerships, taxation and occupational health compensations. Despite substantial efforts in the field of tobacco control, existing measures have not yielded the desired results in curbing tobacco smoking and behavioural economics may be an effective tool to bridge the gap. This study highlights the lack of knowledge on nudging as an effective tool for tobacco control. It is imperative to allocate increased funding to further explore the role of nudging in tobacco control and generate additional data in this area.